Compensation policies and their impact on job satisfaction among employees at the University of Jordan - Mokbel, Sobhiya Abdel Aziz Ahmed (Journal of Economic, Administrative and Legal Sciences, 2018)
This thesis aimed to study the financial compensation policies and their impact on job satisfaction among workers in the University of Jordan, through the theoretical framework and previous related literature, and the results of statistical analysis of the answers of respondents on the measurement tool (questionnaire) prepared for this purpose. The study found the following results: - There is a statistically significant effect at the level of significance (0.05 ≥α) of the policies of financial compensation dimensions (direct and indirect) in the level of job satisfaction in the university of Jordan. The impact was direct financial compensation stronger than the indirect financial compensation in the Jordanian university policies. - The perceptions of the respondents towards the realization of employees to nature and the application of the compensation of financial policies came moderately stood in the university (2.7) from (4). - There are statistically significant differences at the level of significance (0.05≥α) for answers to job satisfaction scale due to the difference in the level of education variables, any satisfaction for the benefit of the highest qualified holds doctorate. Administrative level, for the benefit of senior management, and the level of salary, for the benefit of getting a salary (1,000 dinars and over) in the Jordanian university. The study presented several recommendations, most notably the work to build scientific and objective ways, in an equal financial compensation policies, between universities, to avoid the financial and administrative corruption, and to achieve job satisfaction among workers at university of Jordan. The study also recommends the need for further studies in this field in other Jordanian universities to achieve internal and external justice.